The Effect of Infant Massage Using Virgin Coconut Oil (VCO) on Increasing Infant Appetite at the Bongo II Community Health Center Technical Implementation Unit - Syntia Ramadani; Retno Dewi Prisusanti (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Injectable contraception remains one of the most widely used family planning methods among couples of reproductive age. However, the success of this method is strongly influenced by the level of knowledge and attitudes of acceptors, which in practice are often still inadequate. This study aimed to evaluate the effectiveness of injectable contraceptive educational videos in improving the knowledge and attitudes of injectable contraceptive acceptors at TPMB Siti Juhariyah. The study employed a quantitative approach with a quasi-experimental one-group pretest–posttest design. A total of 30 injectable contraceptive acceptors were selected as samples using purposive sampling techniques. The intervention consisted of providing an educational video on injectable contraception, followed by the assessment of participants’ knowledge and attitudes before and after the intervention using structured questionnaires. Data were analyzed using statistical tests to determine differences between pretest and posttest scores. The results showed a significant increase in acceptors’ knowledge, which shifted from moderate and low categories to a good category after the educational video intervention. In addition, the acceptors’ attitudes toward the use of injectable contraception also demonstrated a significant positive change. Based on these findings, it can be concluded that injectable contraceptive educational videos are effective in improving the knowledge and attitudes of acceptors. Therefore, educational videos can be utilized as a supportive counseling medium in family planning services to enhance the quality of contraceptive care in independent midwifery practices.